The impact of supply‐side electronic integration on customer service performance. Issue 6 (27th July 2013) - Xue, Ling; Ray, Gautam; Sambamurthy, Vallabh
Abstract: Although information technologies have been expected to directly enhance firm performance in specific value chain activities (e.g., supplier performance or customer service performance), their advanced capabilities offer the promise of organizational integration and spill‐over benefits. Enterprise systems provide firms with platforms for electronically integrating their supplier and demand chain activities. Spill‐over benefits refer to the impacts that occur when IT investments in one organizational domain benefit performance in a different value chain side of the firm. Supply‐side electronic integration (SEI) refers to the use of electronic means to integrate the exchange of information and transactions with suppliers through enterprise systems. In our research, we examine whether SEI generates spill‐over effects on customer service performance, over and beyond firms' direct investments in customer‐side digitization. We also examine whether structural attributes of the firm (e.g., vertical integration, diversification, and centralization) moderate the effects of supply‐side electronic integration on customer service performance. Our analysis of a secondary dataset of InformationWeek 500 firms shows that SEI helps firms realize cost‐savings in their customer service performance, especially if they are less vertically integrated. In addition, SEI investments help diversified and centralized firms achieve cross‐selling with their customers. We also find that SEI is more likely to help decentralized and diversified firms achieve customization in their customer service activities. These results suggest that SEI helps firms achieve twin goals in customer service: cost reduction and revenue expansion. Overall, our research reveals how supply‐side electronic integration could generate benefits in customer service performance in firms.